Ozone induces stomatal narrowing in European and Siebold's beeches: A comparison between two experiments of free-air ozone exposure. (January 2015) - Hoshika, Yasutomo; Watanabe, Makoto; Kitao, Mitsutoshi; Häberle, Karl-Heinz; Grams, Thorsten E.E.; Koike, Takayoshi; Matyssek, Rainer
Abstract: Stomata tend to narrow under ozone (O3 ) impact, leading to limitation of stomatal O3 influx. Here, we review stomatal response under recently conducted free-air O3 exposure experiments on two species of the same tree genus: Fagus sylvatica at Kranzberg Forest (Germany) and F. crenata at Sapporo Experimental Forest (Japan). Both beeches exhibited reduction in stomatal conductance ( g s ) by 10–20% under experimentally enhanced O3 regimes throughout the summer relative to ambient-air controls. Stomatal narrowing occurred, in early summer, in the absence of reduced carboxylation capacity of Rubisco, although photosynthetic net CO2 uptake rate temporarily reflected restriction to some minor extent. Observed stomatal narrowing was, however, diminished in autumn, suggesting gradual loss of stomatal regulation by O3 . Monotonic decline in g s with cumulative O3 exposure or flux in current modeling concepts appear to be unrealistic in beech. Highlights: We review stomatal response under recently conducted free-air O3 exposure experiments on beech. O3 reduced stomatal conductance by 10–20% throughout the summer in European and Siebold's beech. Stomatal closure occurred without reduced carboxylation capacity of Rubisco in early summer. Observed stomatal closure was, however, diminished in autumn in both beeches. Stomatal closure is a primary response in beech trees to chronic O3 impact. Abstract : Stomata narrow under ozone stress in up-growing (beyond sapling stage) and maturing trees of Siebold's and European beech, respectively.